Oxygen-enhanced lung magnetic resonance imaging: influence of inversion pulse slice selectivity on inversion recovery half-Fourier single-shot turbo spin-echo signal - Takenaka, Daisuke; Puderbach, Michael; Ohno, Yoshiharu; Risse, Frank; Ley, Sebastian; Sugimura, Kazuro; Kauczor, Hans-Ulrich (Japanese journal of radiology, 2011)
The purpose of this study was to evaluate in vivo the influence of inversion pulse slice selectivity on oxygen-enhanced magnetic resonance imaging (MRI).
Gesehen am 20.10.2022